(untitled) (Stato, Chiese e pluralismo confessionale, 2012)
Il contributo, sottoposto a valutazione, è destinato alla pubblicazione negli Atti del Convegno di studio organizzato dall’ADEC sul tema “Dimensione pubblica e fattore religioso – Stato attuale e prospettive” (Bari, Aula Magna “Aldo Moro”, 17-18 settembre 2009), in corso di stampa SOMMARIO: 1. La posizione del Presidente della Repubblica Giorgio Napolitano – 2. Laicismo e anticlericalismo – 3. Un’auspicabile prospettiva circa la laicità. ABSTRACT An event that has sparked discussions on neutrality and assumed centrality in the debate on the public dimension of the religious factor is related to the non-participation of Benedict XVI at the inauguration of the academic year at the University of Rome "La Sapienza", scheduled for January 17, 2008. In its judgment no. 203/1989, the Constitutional Court stated that neutrality "does not imply indifference to religion but the state guarantee for the protection of freedom of religion, under the religious and cultural pluralism." The debate on the issue of the University "La Sapienza" has fueled confusion about the meaning of the word to make the invisible boundary between neutrality, laicism and anti-clericalism. Decisive contribution to the construction of some carefully sentinels, among which there are those who have authoritatively explained that neutrality is to be understood: "... not as an attitude of estrangement, indifference or hostility of the state and its elites, with respect to the religious consciousness of the people, under the confessional pluralism, atheism is not excluded, but the protection of the equal freedom of all faiths (...) The true neutrality and the true faith are made to compete fairly in the conduct man to the full meaning of the days that are given to live". KEYWORDS: Neutrality, public dimension of the religious factor, laicism, anti-clericalism